1994
DOI: 10.1159/000276609
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis Presented Acute Hearing Loss and Vertigo

Abstract: A case of multiple sclerosis with acute deafness and dizziness as initial symptoms was reported. The pure-tone audiometry showed a high-frequency sensorineural hearing loss; in the auditory evoked brain stem response (ABR), the left side had a normal peak I with an absence of subsequent peaks. In the equilibrium test, Bruns’ nystagmus was present, and the caloric test demonstrated CP on the left side. MRI disclosed a high-intensity lesion in the cerebellar peduncle (T2-weighted image). With steroid therapy, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…The most common type of hearing loss (after normal hearing) for the group of subjects with MS and for the group of control subjects without MS was sensorineural hearing loss. This is the most common type of hearing loss typically reported in articles of both individuals with and without MS. Additionally, this type of hearing loss is consistent with the disease process of MS and prior investigations have suggested that sensorineural hearing loss in individuals with MS is due to swelling and/or scarring in the lower portions of the central auditory pathways or in the cochlear nerve [24,26,28,30,[33][34][37][38] …”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The most common type of hearing loss (after normal hearing) for the group of subjects with MS and for the group of control subjects without MS was sensorineural hearing loss. This is the most common type of hearing loss typically reported in articles of both individuals with and without MS. Additionally, this type of hearing loss is consistent with the disease process of MS and prior investigations have suggested that sensorineural hearing loss in individuals with MS is due to swelling and/or scarring in the lower portions of the central auditory pathways or in the cochlear nerve [24,26,28,30,[33][34][37][38] …”
Section: Discussionsupporting
confidence: 81%
“…This is consistent with Noffsinger et al [1], as well as research on the general population [3,[6][7], which suggests that most hearing losses are bilateral rather than unilateral. It does, however, contradict case-study reports of individuals with MS presenting sudden Sensorineural hearing loss [24][25][26][27][28][29][30][31][32][33][34][35][36]. In those reports, the loss was typically unilateral but returned to normal or previous HLs after a given period of time (sometime after the exacerbation in symptoms).…”
Section: Discussionmentioning
confidence: 83%
“…In MS there is a high incidence of vestibular disturbances, and some human conditions, such as vertigo, can be caused by inflammatory responses in the brainstem and cerebellum (45)(46)(47)(48), similar to what is observed in nonclassical EAE. The factors that determine the spatial localization of these lesions are not well understood, and the nonclassical model presented in this report holds promise in defining the mechanisms underlying these phenomena.…”
Section: Discussionmentioning
confidence: 67%
“…2,4,13 In our patient no brainstem demyelinating lesion was detected, but brain MRI was performed after a month of SSNHL initiation and after intratympanic dexamethasone administration. 2,5,[7][8][9][10][11] The same BAEPs pattern is present in most of the cases with definite MS and SSNHL. 13 There has been debate on the precise site of demyelination in definite MS patients with SSNHL.…”
Section: Discussionmentioning
confidence: 99%